2011
DOI: 10.1115/1.4003588
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation of Single and Multiple Square Jets in Cross-Flow

Abstract: Direct numerical simulations (DNSs) have been carried out for single and multiple square jets issuing normally into a cross-flow, with the primary aim of studying the flow structures and interaction mechanisms associated with the jet in cross-flow (JICF) problems. The single JICF configuration follows a similar study previously done by Sau et al. (2004, Phys. Rev. E, 69, p. 066302) and the multiple JICF configurations are arranged side-by-side in the spanwise direction with a jet-to-jet adjacent edge distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Due to the merging process whilst the vortex roller moving downstream, the scale of K-H vortices increases with the distance, similar to that in a free jet flow. Overall present observations are in good agreement with previous experimental and numerical predictions [12]. The influence of the streamline injection angle variations on the flow structures in jet cross-flow interaction has been assessed.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Due to the merging process whilst the vortex roller moving downstream, the scale of K-H vortices increases with the distance, similar to that in a free jet flow. Overall present observations are in good agreement with previous experimental and numerical predictions [12]. The influence of the streamline injection angle variations on the flow structures in jet cross-flow interaction has been assessed.…”
Section: Resultssupporting
confidence: 81%
“…Following a previous numerical study of Sau et al [11], a computational grid of 241 points in the streamwise (with 11 points in the jet domain), 81 points in the wall normal, and 61 points in the spanwise direction (with 11 points in the jet domain) is adopted. Both domain influence and grid refinement studies have been carried out [12]. For example, simulations were performed on domain sizes of 24D × 9D × 8D and 24D × 6D × 12D (using similar grid resolutions and distributions) and computational meshes of 192 × 65 × 49 and 361 × 121 × 91 (both applied to the baseline domain), respectively.…”
Section: Problem Definitionsmentioning
confidence: 99%
“…13, contours of passive-scalar at several jet downstream XY planes and for different jet-to-crossflow velocity ratios are used to illustrate the main vortex structure characterizing the JICF configuration such as the Counter-Rotating Vortex Pair (CRVP). These contours clearly show the classic kidney-shaped Counter-Rotating Vortex Pair (CRVP), as seen in other studies (Strzelecki et al, 2009;Yao and Maidi, 2011;Salinas-Vazquez et al, 2005). Note that the kidney shape is evident even near the jet exit at x/l j = 1.…”
Section: Ajassupporting
confidence: 80%
“…Thus, steady Reynolds-averaged Navier-Stokes Simulation (RANS) is still the primary simulation approach used in this study. Nevertheless, for a JICF problem which is highly complex with a lot of streamline curvature and anisotropy, high resolution methods, such as Large Eddy Simulation (LES) (Jouhaud et al, 2007) and Direct Numerical Simulation (DNS) (Yao and Maidi, 2011), have been found outperforming RANS. However, the expensive computational cost could be a barrier to use these two methods.…”
Section: Methodsmentioning
confidence: 99%